2018
DOI: 10.2217/fon-2018-0423
|View full text |Cite
|
Sign up to set email alerts
|

GEN-1 Immunotherapy for the Treatment of Ovarian Cancer

Abstract: GEN-1 is a gene-based immunotherapy, comprising a human IL-12 gene expression plasmid and a synthetic plasmid delivery system, delivered intraperitoneally (ip.) to produce local and persistent levels of a pleiotropic immunocytokine, IL-12, at the tumor site in patients with advanced ovarian cancer. The goal of local and persistent IL-12 delivery is to remodel the highly immunosuppressive tumor microenvironment to favor immune stimulation while avoiding serious systemic toxicities, a major limitation of recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Although chemotherapy is the established treatment for SOC, the survival rate remains low, and it is highly anticipated that new treatments will be successfully developed [9,10]. Therapies, such as targeted treatment and immunotherapy, are needed to combat this disease [11,12]. Recently, various of proteins have been found highly expressed in SOC tissues, some of which (including AIF1 and WNK1) have become potential therapeutic targets for SOC [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although chemotherapy is the established treatment for SOC, the survival rate remains low, and it is highly anticipated that new treatments will be successfully developed [9,10]. Therapies, such as targeted treatment and immunotherapy, are needed to combat this disease [11,12]. Recently, various of proteins have been found highly expressed in SOC tissues, some of which (including AIF1 and WNK1) have become potential therapeutic targets for SOC [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that miR-3200 affects the transcriptional ability of several genes, such as, GEN1,TMTC4, TSC22D1, SGK1, ITGB5,SNX1, SUV39H1, CBX5,HOXA7, RAD54L.The study indicates that the immunotherapy based on GEN1 is good for ovarian cancer [ 17 ]. Moreover, the deletion of TMTC4 activates the unfolded protein [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…GEN-1 was first investigated as an intraperitoneal injection and gained traction after a phase I study demonstrated that platinum-sensitive ovarian cancer patients derived an ORR of 50.0% (6/12) with a DCR of 91.7% (11/12) and good tolerability [ 329 ]. However, multiple phase I and II trials shortly followed involving platinum-resistant cohorts which failed to replicate these results [ 330 ]. Given the above, the focus has since shifted to applying GEN-1 as an adjunct to neoadjuvant chemotherapy for curative intent in ovarian cancer patients, as seen in the phase I OVATION-I trial which found an ORR of 85.7% (12/14) with CR in 14.3% (2/14) of patients and subsequent surgical resection of all macroscopic disease (R0) achieved in 64.3% (9/13) of participants [ 331 ].…”
Section: Targeting Strategies Against Myeloid Cells For Cancer Immuno...mentioning
confidence: 99%